Coenzyme Q10, Ageing and the Nervous System: An Overview - David Mantle; Robert A. Heaton; Iain P. Hargreaves (MDPI AG, 2021)
The ageing brain is characterised by changes at the physical, histological, biochemical and physiological levels. This ageing process is associated with an increased risk of developing a number of neurological disorders, notably Alzheimer's disease and Parkinson's disease. There is evidence that mitochondrial dysfunction and oxidative stress play a key role in the pathogenesis of such disorders. In this article, we review the potential therapeutic role in these age-related neurological disorders of supplementary coenzyme Q10, a vitamin-like substance of vital importance for normal mitochondrial function and as an antioxidant. This review is concerned primarily with studies in humans rather than in vitro studies or studies in animal models of neurological disease. In particular, the reasons why the outcomes of clinical trials supplementing coenzyme Q10 in these neurological disorders is discussed.